Active energy ray-curable pressure-sensitive adhesive composition, cured product, and pressure-sensitive adhesive sheet

The active energy ray-curable adhesive composition, formed by a specific reaction product of polyol and aliphatic polyisocyanate with hydroxyl group-containing mono(meth)acrylate, addresses bending resistance issues in foldable devices, ensuring adhesion and durability.

JP7616261B2Active Publication Date: 2025-01-17ARAKAWA CHEM IND LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023052554
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2025-01-17
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

Existing adhesive compositions for foldable devices fail to provide adequate bending resistance, leading to issues such as peeling of the adhesive layer when the device is folded.

Method used

A specific formulation of an active energy ray-curable adhesive composition comprising a reaction product of polyol and aliphatic polyisocyanate with hydroxyl group-containing or isocyanate group-containing mono(meth)acrylate, along with specific ratios and types of (meth)acrylates, which are cured to form a pressure-sensitive adhesive sheet.

Benefits of technology

The adhesive composition exhibits excellent bending resistance, maintaining adhesion and preventing peeling, with improved durability and curability, suitable for foldable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616261000001
    Figure 0007616261000001
Patent Text Reader

Abstract

To provide an active energy ray-curable adhesive composition, a cured product, and an adhesive sheet which have good bending resistance.SOLUTION: The present invention relates to the active energy ray-curable adhesive composition containing: (A) a urethane (meth)acrylate which is a reaction product of (a1) a polyol, (a2) an aliphatic polyisocyanate, and (a3-1) a hydroxyl group-containing mono(meth)acrylate or (a3-2) an isocyanate group-containing mono(meth)acrylate and has a weight average molecular weight of 30,000 or more and 150,000 or less; (B) a (meth)acrylate having one ethylenically unsaturated double bond in the molecule and having no hydroxyl group; and (C) a primary hydroxyl group-containing mono(meth)acrylate. The component (B) contains a (meth)acrylate (b1) whose homopolymer has a glass transition temperature lower than -5°C and / or a (meth)acrylate (b2) whose homopolymer has a glass transition temperature of -5°C or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an active energy ray-curable pressure-sensitive adhesive composition, a cured product, and a pressure-sensitive adhesive sheet. [Background technology]

[0002] In recent years, adhesive compositions having properties suitable for foldable devices (for example, foldable image display devices, etc.) have been developed. However, it is known that when a foldable device is folded, a strong load is applied to various layers constituting the device, resulting in various problems. For example, when the device is folded, peeling or the like may occur in the layer of the adhesive composition (in this disclosure, the "layer of the adhesive composition" is also referred to as the "cured product"), and there is a demand for a cured product that does not peel or the like even when folded.

[0003] Patent Document 1 discloses an active energy ray-curable pressure-sensitive adhesive composition containing a urethane (meth)acrylate, an alkyl mono(meth)acrylate, and a primary hydroxyl group-containing mono(meth)acrylate (in the present disclosure, the "active energy ray-curable pressure-sensitive adhesive composition" is also referred to as the "pressure-sensitive adhesive composition"). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-037689 A Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 did not consider bending resistance.

[0006] An object of the present disclosure is to provide an active energy ray-curable pressure-sensitive adhesive composition having good bending resistance, a cured product thereof, and a pressure-sensitive adhesive sheet. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a specific active energy ray-curable pressure-sensitive adhesive composition, a cured product thereof, and a pressure-sensitive adhesive sheet having the cured product. The present disclosure has been made to solve at least a part of the above-mentioned problems, and can be realized as the following aspects or application examples.

[0008] That is, the present disclosure relates to the following items: (Item 1) (A) a urethane (meth)acrylate (A) which is a reaction product of (a1) a polyol, (a2) an aliphatic polyisocyanate, and (a3-1) a hydroxyl group-containing mono(meth)acrylate or (a3-2) an isocyanate group-containing mono(meth)acrylate and has a weight average molecular weight of 30,000 or more and 150,000 or less; (B) a (meth)acrylate having one ethylenically unsaturated double bond in the molecule and no hydroxy group; (C) a primary hydroxyl group-containing mono(meth)acrylate, The component (B) contains a (meth)acrylate (b1) having a glass transition temperature of less than −5° C. when made into a homopolymer and / or a (meth)acrylate (b2) having a glass transition temperature of −5° C. or higher when made into a homopolymer, When the total amount of the components (A), (B), and (C) is 100 mass%, The content of the component (A) in terms of solid content is more than 35% by mass and 55% by mass or less, The content of the component (B) in terms of solid content is 30% by mass or more and 55% by mass or less, The content of the component (C) in terms of solid content is 9% by mass or more and less than 20% by mass, When the total amount of the (meth)acrylates constituting the component (B) is 100 mass%, The content of the component (b1) in terms of solid content is 71% by mass or more and 100% by mass or less, The content of the component (b2) in terms of solid content is 0% by mass or more and 29% by mass or less; An active energy ray-curable pressure-sensitive adhesive composition. (Item 2) 2. The active energy ray-curable pressure-sensitive adhesive composition according to item 1, wherein the active energy ray-curable pressure-sensitive adhesive composition does not contain 1% by mass or more of a resin having a softening point of 90° C. or higher, relative to 100% by mass of the total of the components (A), (B), and (C). (Item 3) 3. A cured product of the active energy ray-curable pressure-sensitive adhesive composition according to item 1 or 2. (Item 4) Item 4. A pressure-sensitive adhesive sheet having the cured product according to item 3 on at least one surface of a substrate. Effect of the Invention

[0009] The active energy ray-curable pressure-sensitive adhesive composition, cured product, and pressure-sensitive adhesive sheet of the present disclosure can exhibit good bending resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Throughout the present disclosure, the range of the values ​​of each physical property, content, etc. may be set appropriately (for example, by selecting from the upper and lower limit values ​​described in each item below). Specifically, when A1, A2, A3, etc. are exemplified as the lower limit of the value α and B1, B2, B3, etc. are exemplified as the upper limit of the value α, the range of the value α is exemplified as A1 or more, A2 or more, A3 or more, B1 or less, B2 or less, B3 or less, A1 to B1, A1 to B2, A1 to B3, A2 to B1, A2 to B2, A2 to B3, A3 to B1, A3 to B2, A3 to B3, etc. In addition, in the present disclosure, "to" is used to mean that the values ​​described before and after it are included as the lower limit and upper limit. Below, the components and manufacturing method of the present disclosure will be described in detail.

[0011] <Component (A)> The component (A) is a reaction product of (a1) a polyol, (a2) an aliphatic polyisocyanate, and (a3-1) a hydroxyl group-containing mono(meth)acrylate or (a3-2) an isocyanate group-containing mono(meth)acrylate, and is a urethane (meth)acrylate having a weight average molecular weight of 30,000 or more and 150,000 or less.

[0012] <Component (a1)> By using a polyol as the (a1) component, the cured product of the present disclosure has excellent transparency and bending resistance. Examples of the (a1) component include polyether polyol, polyester polyol, polymer polyol, poly(meth)acrylic polyol, polycarbonate polyol, castor oil-based polyol, and polyolefin polyol. In the present disclosure, (meth)acrylic refers to acrylic and / or methacrylic.

[0013] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, and polytetramethylene glycol.

[0014] The polyether polyol may be a commercially available product. Examples of the product include polyether diol (product name "ADEKA POLYETHER P", manufactured by ADEKA Corporation), polyether triol (product name "ADEKA POLYETHER G", manufactured by ADEKA Corporation), polyether tetraol (product name "ADEKA POLYETHER EDP", manufactured by ADEKA Corporation), polyethylene glycol (product name "Polyethylene Glycol #1,540", manufactured by Nacalai Tesque, Inc.), dipropylene glycol (product name "Dipropylene Glycol", manufactured by Junsei Chemical Co., Ltd.), polypropylene glycol (product name "Polypropylene Glycol 400", manufactured by Kishida Chemical Co., Ltd.), and polytetramethylene ether glycol (product names "PTMG650", "PTMG1000", "PTMG2000", "PTMG3000", manufactured by Mitsubishi Chemical Corporation).

[0015] The polyester polyol may be a commercially available product. Examples of such products include high refractive index grade polyester polyol (product name "Polylite RX-4800", manufactured by DIC Corporation), high crystallinity grade polyester polyol (product names "Polylite OD-X-2523" and "Polylite OD-X-2547", manufactured by DIC Corporation), transparent grade polyester polyol (product names "Polylite OD-X-2420" and "Polylite OD-X-2692", manufactured by DIC Corporation), high adhesion grade polyester polyol (product name "Polylite OD-X-21 Examples of such polyols include "PLACCEL 08", manufactured by DIC Corporation), polyester polyol (product name "ETERNACOLL 3000", manufactured by Ube Industries, Ltd.), polycaprolactone polyol (product name "POLYLITE OD-X-2155", manufactured by DIC Corporation), polycaprolactone diol (product name "PLACCEL 200", manufactured by Daicel Corporation), polycaprolactone triol (product name "PLACCEL 300", manufactured by Daicel Corporation), and polycaprolactone tetraol (product name "PLACCEL 400", manufactured by Daicel Corporation).

[0016] The polymer polyol may be a commercially available product. Examples of the product include polymer polyol (product name "Sharp Flow", manufactured by Sanyo Chemical Industries, Ltd.) and polymer polyol (product name "Exenol", manufactured by AGC Corporation).

[0017] The poly(meth)acrylic polyol may be a commercially available product. Examples of the product include acrylic polyol (product name "acrylic polyol #6000", manufactured by Taisei Fine Chemical Co., Ltd.), acrylic polyol (product name "ETERAC7315-XS-60", manufactured by Changxing Materials Industrial Co., Ltd.), and acrylic polyol (product name "acrylic polyol PC #5984", manufactured by Toei Kasei Co., Ltd.).

[0018] The polycarbonate polyol may be a commercially available product. Examples of the product include polycarbonate diol (product name "Benebiol", manufactured by Mitsubishi Chemical Corporation), (product name "Nipporun", manufactured by Tosoh Corporation), (product name "Duranol series", manufactured by Asahi Kasei Corporation), and the like.

[0019] The castor oil-based polyol may be a commercially available product. Examples of such products include castor oil-based polyol (product name "URIC H series", manufactured by Ito Oil Mills, Ltd.) and castor oil-based polyol (product names "Castor Oil-Based Polyol HS CM-025P" and "Castor Oil-Based Polyol HS CM-075P", manufactured by Toyokuni Oil Mills, Ltd.).

[0020] Examples of polyolefin polyols include hydroxyl-containing polybutadiene, hydrogenated hydroxyl-containing polybutadiene, hydroxyl-containing polyisoprene, hydrogenated hydroxyl-containing polyisoprene, hydroxyl-containing chlorinated polypropylene, and hydroxyl-containing chlorinated polyethylene.

[0021] The polyolefin polyol may be a commercially available product. Examples of the product include polybutadiene diol (product names "Poly bd R-45HT" and "Poly bd R-15HT" manufactured by Idemitsu Kosan Co., Ltd.) (product names "NISSO-PB B-1000", "NISSO-PB B-2000", "NISSO-PB G-1000", and "NISSO-PB G-2000" manufactured by Nippon Soda Co., Ltd.), and hydrogenated polybutadiene diol (product names "NISSO-PB GI-1000" and "NISSO-PB GI-2000" manufactured by Nippon Soda Co., Ltd.).

[0022] Examples of the upper limit of the number average molecular weight of the (a1) component include 13,000, 12,000, 11,000, 10,000, 9,000, 8,000, 7,000, 6,000, 5,000, 4,000, 3,000, 2,000, 1,000, 900, and 800, and examples of the lower limit include 12,000, 11,000, 10,000, 9,000, 8,000, 7,000, 6,000, 5,000, 4,000, 3,000, 2,000, 1,000, 900, 800, and 700. The number average molecular weight of the (a1) component is preferably 700 or more and 13,000 or less, since the cured product has excellent adhesion and step conformability. If the number average molecular weight of the (a1) component is less than the lower limit, the cured product tends to be hard, and if it is more than the upper limit, the cured product tends to be soft, so if it is within the preferred range, the adhesive strength and step conformability tend to be good. In the present disclosure, the number average molecular weight can be determined by the method described in JIS K7252-1:2016.

[0023] The upper limit of the number of hydroxyl groups of the (a1) component is 3.0, 2.8, 2.5, 2.3, 2.0, 1.8, etc., and the lower limit is 2.8, 2.5, 2.3, 2.0, 1.8, 1.5, etc. The number of hydroxyl groups of the (a1) component is preferably 1.5 to 3.0, more preferably 1.8 to 2.5, since the cured product has excellent step-following properties and processability. In this disclosure, the number of hydroxyl groups can be determined by the method described in JIS K1557-1:2007. Specifically, the number of hydroxyl groups can be determined by the acetylation method. In this disclosure, "step-following properties" and "processability" have the same meaning as those described in JP-A-2020-037689.

[0024] Examples of upper limits for the content of the (a1) component (converted to solid content) relative to 100% by mass (converted to solid content) of the total amount of the (a1) component, the (a2) component, and the (a3-1) component or the (a3-2) component are 98, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, and 5% by mass, and examples of lower limits for the same are 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 5, and 1% by mass. In one embodiment, the content of the (a1) component (in terms of solid content) in the total amount (100 mass% (in terms of solid content) of the (a1) component, the (a2) component, and the (a3-1) component or the (a3-2) component is preferably about 1 to 98 mass%.

[0025] <(a2) component> The component (a2) is an aliphatic polyisocyanate. Examples of the component (a2) include an aliphatic diisocyanate, an aliphatic triisocyanate, and an aliphatic tetraisocyanate.

[0026] Examples of the component (a2) include linear aliphatic polyisocyanates, branched aliphatic polyisocyanates, and alicyclic aliphatic polyisocyanates.

[0027] Examples of linear aliphatic diisocyanates include trimethylene diisocyanate, tetramethylene diisocyanate, 1,5-pentamethylene diisocyanate, hexamethylene diisocyanate, octamethylene diisocyanate, and decamethylene diisocyanate.

[0028] Examples of branched aliphatic diisocyanates include methyl 2,6-diisocyanatohexanoate and trimethylhexamethylene diisocyanate.

[0029] Examples of alicyclic aliphatic diisocyanates include dicyclohexylmethane 4,4'-diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, cyclohexane-1,4-diylbis(methylene)diisocyanate, 1-methylcyclohexane-2,4-diyldiisocyanate, 1,4-cyclohexane diisocyanate, hydrogenated xylene diisocyanate, hydrogenated tolylene diisocyanate, and norbornene diisocyanate.

[0030] An example of the linear aliphatic triisocyanate is lysine triisocyanate.

[0031] The (a2) component is preferably an aliphatic diisocyanate, more preferably a linear aliphatic diisocyanate and / or an alicyclic aliphatic diisocyanate, because the cured product has excellent durability after a moist heat resistance test and excellent step conformability. In this disclosure, the term "durability after a moist heat resistance test" has the same meaning as that described in JP 2020-037689 A.

[0032] (a2) Number of moles of isocyanate groups in component (NCO (a2) ) and the number of moles of hydroxyl groups in the (a1) component (OH (a1) ) and the ratio (NCO (a2) / OH (a1) The upper limit of the (a2) molar number of isocyanate groups (NCO (a2) ) and the number of moles of hydroxyl groups in the (a1) component (OH (a1) ) and the ratio (NCO (a2) / OH (a1) ) is preferably about 0.5 to 2.0.

[0033] The upper limit of the molecular weight of the (a2) component is 1,000, 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, 300, 250, 200, 150, 100, 50, 25, etc., and the lower limit is 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, 300, 250, 200, 150, 100, 50, 25, 10, etc. In one embodiment, the molecular weight of the (a2) component is preferably 10 to 1,000. In the present disclosure, when simply described as "molecular weight", it means a value calculated based on atomic weight.

[0034] The upper limit of the content ratio of the (a1) component to the (a2) component (mass ratio, solid content equivalent, [(a1) component / (a2) component]) is 99 / 1, 95 / 5, 90 / 10, 85 / 15, 80 / 20, 75 / 25, 70 / 30, 65 / 35, 60 / 40, 55 / 45, 50 / 50, 45 / 55, 40 / 60, 35 / 65, 30 / 70, 25 / 75, 20 / 80, Examples of the upper limit include 95 / 5, 90 / 10, 85 / 15, 80 / 20, 75 / 25, 70 / 30, 65 / 35, 60 / 40, 55 / 45, 50 / 50, 45 / 55, 40 / 60, 35 / 65, 30 / 70, 25 / 75, 20 / 80, 15 / 85, 10 / 90, 5 / 95, 1 / 99, etc. In one embodiment, the content ratio of the (a1) component to the (a2) component (mass ratio, solid content equivalent, [(a1) component / (a2) component]) is preferably about 1 / 99 to 99 / 1.

[0035] Examples of upper limits for the content of the (a2) component (converted to solid content) relative to 100% by mass (converted to solid content) of the total amount of the (a1) component, the (a2) component, and the (a3-1) component or the (a3-2) component are 98, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, and 5% by mass, and examples of lower limits for the same are 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 5, and 1% by mass. In one embodiment, the content of the (a2) component (in terms of solid content) in the total amount (100 mass% (in terms of solid content) of the (a1) component, the (a2) component, and the (a3-1) component or the (a3-2) component is preferably about 1 to 98 mass%.

[0036] <Component (a3-1) or Component (a3-2)> The (a3-1) component is a hydroxyl group-containing mono(meth)acrylate, and the (a3-2) component is an isocyanate group-containing mono(meth)acrylate. By using the (a3-1) or (a3-2) component, the adhesive composition has excellent curability. When the adhesive composition is produced without the (a3-1) or (a3-2) component, or by using, for example, a hydroxyl group-containing photopolymerization initiator as an alternative to the (a3-1) or (a3-2) component, poor curing occurs, and the cured product becomes too soft at room temperature. When cutting a substrate or the like containing such a cured product, the cured product tends to adhere to the surface of the blade of the cutting machine (i.e., the processability becomes poor), so an adhesive composition that does not contain the (a3-1) or (a3-2) component is not preferred. When the adhesive composition is produced by using, for example, a hydroxyl group-containing photopolymerization initiator as an alternative to the (a3-1) or (a3-2) component, the transparency also becomes poor, so it is not preferred.

[0037] Examples of the (a3-1) component include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, glycerol mono(meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate.

[0038] An example of the component (a3-2) is 2-isocyanatoethyl (meth)acrylate.

[0039] The (a3-1) or (a3-2) component is preferably a hydroxyl-containing mono(meth)acrylate having from 5 to 10 carbon atoms, and more preferably one or more selected from the group consisting of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, because the pressure-sensitive adhesive composition has excellent curing properties.

[0040] The upper limit of the number of carbon atoms contained in the (a3-1) or (a3-2) component is 60, 50, 40, 30, 20, 10, 9, 8, 7, 5, 4, etc., and the lower limit is 50, 40, 30, 20, 10, 9, 8, 7, 5, 4, 3, etc. In one embodiment, the number of carbon atoms contained in the (a3-1) or (a3-2) component is preferably about 4 to 60.

[0041] Examples of the upper limit of the molecular weight of the (a3-1) component or the (a3-2) component include 1,000, 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, 300, 250, 200, 150, 100, 50, 25, etc., and examples of the lower limit include 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, 300, 250, 200, 150, 100, 50, 25, 10, etc. In one embodiment, the molecular weight of the (a3-1) component or the (a3-2) component is preferably 10 to 1,000.

[0042] Examples of upper limits for the content ratio of component (a1) or component (a2) to component (a3-1) or component (a3-2) (mass ratio, solid content equivalent, [component (a1) or component (a2) / component (a3-1) or component (a3-2)]) are 99.9 / 0.1, 99.5 / 0.5, 99 / 1, 95 / 5, 90 / 10, 85 / 15, 80 / 20, 75 / 25, etc., and examples of lower limits include 99.5 / 0.5, 99 / 1, 95 / 5, 90 / 10, 85 / 15, 80 / 20, 75 / 25, 70 / 30, etc. In one embodiment, the content ratio of the (a1) or (a2) component to the (a3-1) or (a3-2) component (mass ratio, solid content equivalent, [(a1) or (a2) component / (a3-1) or (a3-2) component]) is preferably about 70 / 30 to 99.9 / 0.1.

[0043] The upper limit of the content (solid content) of the (a3-1) or (a3-2) component in 100% by mass (solid content) of the total of the (a1), (a2), and (a3-1) or (a3-2) components is 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5% by mass, and the lower limit is 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5, 0.1% by mass, etc. In one embodiment, the content (solid content) of the (a3-1) or (a3-2) component in 100% by mass (solid content) of the total of the (a1), (a2), and (a3-1) or (a3-2) components is preferably about 0.1 to 20% by mass.

[0044] <Other additives that can be added to component (A)> Component (A) may contain various additives as necessary, such as a catalyst, a crystal nucleating agent, a crystallization promoter, and a chain transfer agent.

[0045] The (A) component may be obtained by reacting the (a1) component with the (a2) component to produce an isocyanate-terminated urethane prepolymer, and then reacting the isocyanate-terminated urethane prepolymer with the (a3-1) component. The reaction conditions are usually a temperature of about 70 to 85°C and a reaction time of about 1 to 5 hours. The ratio of the isocyanate-terminated urethane prepolymer to the (a3-1) component may be such that the ratio (NCO / OH) of the number of moles of isocyanate groups (NCO) in the former to the number of moles of hydroxyl groups (OH) in the latter is usually about 0.25 to 1.

[0046] The (A) component may be obtained by reacting the (a1) component with the (a2) component to produce a hydroxyl-terminated urethane prepolymer, and then reacting the hydroxyl-terminated urethane prepolymer with the (a3-2) component. The reaction conditions are usually a temperature of about 70 to 85°C and a reaction time of about 1 to 5 hours. The ratio of the hydroxyl-terminated urethane prepolymer to the (a3-2) component may be such that the ratio (NCO / OH) of the number of moles of isocyanate groups in the latter to the number of moles of hydroxyl groups in the former is usually about 0.5 to 1.

[0047] Examples of upper limits of the weight average molecular weight of component (A) include 150,000, 140,000, 130,000, 120,000, 110,000, 100,000, 90,000, 80,000, 70,000, 60,000, 50,000, and 40,000, and examples of lower limits include 140,000, 130,000, 120,000, 110,000, 100,000, 90,000, 80,000, 70,000, 60,000, 50,000, 40,000, and 30,000. The weight average molecular weight of the (A) component is 30,000 or more and 150,000 or less, preferably 50,000 or more and 110,000 or less, because the cured product has excellent adhesion, step conformability and bending resistance. If the weight average molecular weight of the (A) component is less than the lower limit, the cured product has weak adhesion and tends to have poor bending resistance, and if it is more than the upper limit, the adhesive composition has high viscosity and tends to be difficult to manufacture. In the present disclosure, the weight average molecular weight is a polystyrene equivalent value measured by gel permeation chromatography.

[0048] The upper limit of the number of (meth)acryloyl groups contained in the component (A) is, for example, 15, 10, 8, 6, 4, or 2, and the lower limit is, for example, 10, 8, 6, 4, 2, or 1. In one embodiment, the number of (meth)acryloyl groups contained in the component (A) is preferably about 1 to 15.

[0049] The upper limit of the (meth)acrylic equivalent (g / eq) of component (A) is 150,000, 140,000, 130,000, 120,000, 110,000, 100,000, 90,000, 80,000, 70,000, 60,000, 50,000, 40,000, 30,000, 20,000, and 1 Examples of the upper limit include 140,000, 130,000, 120,000, 110,000, 100,000, 90,000, 80,000, 70,000, 60,000, 50,000, 40,000, 30,000, 20,000, 10,000, and 5,000. In one embodiment, the (meth)acrylic equivalent (g / eq) of the (A) component is preferably about 5,000 to 150,000. In the present disclosure, the (meth)acrylic equivalent is represented by the weight average molecular weight per (meth)acrylic group, and can be calculated by "weight average molecular weight / number of functional groups".

[0050] Examples of the upper limit of the content (solid content) of the (A) component in 100% by mass (solid content) of the total of the (A), (B), and (C) components are 55, 54, 53, 52, 51, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, and 36% by mass, and examples of the lower limit are 54, 53, 52, 51, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, and 35% by mass. In one embodiment, the content (solid content) of the (A) component in 100% by mass (solid content) of the total of the (A), (B), and (C) components is more than 35% by mass and not more than 55% by mass. If the content of component (A) exceeds 55% by mass, the elastic modulus of the cured product increases, and the bending resistance deteriorates, which is not preferred. The smaller the amount of component (A), the better the bending resistance tends to be. If the content of component (A) is 35% by mass or less, the sheet becomes too soft, which is not preferred, as it deteriorates the workability and cuttability of the sheet.

[0051] <(B) component> (B) is a (meth)acrylate having one ethylenically unsaturated double bond in the molecule and no hydroxyl group. The (B) component includes a (meth)acrylate (b1) having a glass transition temperature (also referred to as "Tg" in this disclosure) of less than -5°C when made into a homopolymer and / or a (meth)acrylate (b2) having a glass transition temperature of -5°C or higher when made into a homopolymer. By including the (b1) component in the pressure-sensitive adhesive composition of the present disclosure, the storage modulus is reduced and the foldability is improved. By including the (b2) component in the pressure-sensitive adhesive composition of the present disclosure, the adhesive strength is improved. The "glass transition temperature when made into a homopolymer" is a value described in Wiley-Interscience's "Polymer Handbook".

[0052] As component (b1), tetradecyl methacrylate (Tg: -72°C), 2-ethylhexyl acrylate (Tg: -70°C), ethoxydiethylene glycol acrylate (Tg: -70°C), isooctyl acrylate (Tg: -70°C), ethyl carbitol acrylate (Tg: -67°C), n-octyl acrylate (Tg: -65°C), lauryl methacrylate (Tg: -65°C), isononyl acrylate (Tg: -58°C), n-butyl acrylate (Tg: -56°C), 2-methoxyethyl acrylate (Tg: -5 0°C), isodecyl methacrylate (Tg: -41°C), nonyl acrylate (Tg: -37°C), 2-ethoxyethyl methacrylate (Tg: -31°C), isobutyl acrylate (Tg: -26°C), n-lauryl acrylate (Tg: -23°C), phenoxyethyl acrylate (Tg: -22°C), isostearyl acrylate (Tg: -18°C), 2-ethylhexyl methacrylate (Tg: -10°C), (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate (Tg: -7°C), and the like are examples.

[0053] The component (b1) is preferably 2-ethylhexyl acrylate and / or n-octyl acrylate because of its excellent adhesive strength.

[0054] As the component (b2), 2-methoxyethyl methacrylate (Tg: -2°C), (3-ethyloxetan-3-yl)methyl methacrylate (Tg: 2°C), benzyl acrylate (Tg: 6°C), methyl acrylate (Tg: 8°C), cyclohexyl acrylate (Tg: 15°C), diethylaminoethyl methacrylate (Tg: 16 to 24°C), dimethylaminoethyl methacrylate (Tg: 18°C), n-butyl methacrylate (Tg: 20°C), cyclic trimethylolpropane formal acrylate (Tg: 27°C), n-stearyl acrylate (Tg: 30°C), n-stearyl methacrylate (Tg: 38°C), t-butyl acrylate (Tg: 41°C), glycidyl methacrylate ( Examples of the acrylates include acrylate (Tg: 46°C), isobutyl methacrylate (Tg: 48°C), 3,3,5-trimethylcyclohexyl acrylate (Tg: 52°C), benzyl methacrylate (Tg: 54°C), tetrahydrofurfuryl methacrylate (Tg: 60°C), glycidyl acrylate (Tg: 60°C), ethyl methacrylate (Tg: 65°C), cyclohexyl methacrylate (Tg: 66°C), isobornyl acrylate (Tg: 97°C), methyl methacrylate (Tg: 105°C), t-butyl methacrylate (Tg: 107°C), dicyclopentanyl acrylate (Tg: 120°C), 1-adamantyl acrylate (Tg: 153°C), and 1-adamantyl methacrylate (Tg: 250°C).

[0055] The component (b2) is preferably isobornyl acrylate and / or dicyclopentanyl acrylate because of its excellent adhesive strength.

[0056] Examples of upper limits for the number of carbon atoms in component (B) are 30, 25, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, etc., and examples of lower limits are 25, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, etc. In one embodiment, the number of carbon atoms in component (B) is preferably 6 or more and 15 or less.

[0057] Examples of upper limits of the Tg of the (b1) component include -5, -10, -15, -20, -25, -30, -35, -40, -45, -50, -55, -60, and -65°C, and examples of lower limits include -10, -15, -20, -25, -30, -35, -40, -45, -50, -55, -60, -65, and -70°C. In one embodiment, the Tg of the (b1) component is less than -5°C, and preferably is greater than or equal to -70°C and less than -5°C.

[0058] Examples of the upper limit of the Tg of the (b2) component include 250, 240, 230, 220, 210, 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, 100, 90, 80, 70, 60, 50, 40, 30, 20, 10, and 0° C., and examples of the lower limit include 240, 230, 220, 210, 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, 100, 90, 80, 70, 60, 50, 40, 30, 20, 10, 0, and -5° C. In one embodiment, the Tg of the (b2) component is -5° C. or higher, and preferably -5° C. or higher and about 250° C. or lower.

[0059] Examples of upper limits for the content (in terms of solid content) of the (b1) component relative to 100 mass% (in terms of solid content) of the total of the (meth)acrylates constituting the (B) component include 100, 99, 98, 97, 96, 95, 94, 93, 92, 91, 90, 89, 88, 87, 86, 85, 84, 83, 82, 81, 80, 79, 78, 77, 76, 75, 74, 73, and 72 mass%, and examples of lower limits include 99, 98, 97, 96, 95, 94, 93, 92, 91, 90, 89, 88, 87, 86, 85, 84, 83, 82, 81, 80, 79, 78, 77, 76, 75, 74, 73, 72, and 71 mass%, and the like. In one embodiment, the content (in terms of solid content) of the component (b1) relative to a total of 100% by mass (in terms of solid content) of the (meth)acrylate constituting the component (B) is 71 to 100% by mass.

[0060] Examples of upper limits for the content (in terms of solid content) of the (b2) component relative to a total of 100 mass% (in terms of solid content) of the (meth)acrylates constituting the (B) component include 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, and 1 mass%, and examples of lower limits include 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, and 0 mass%,. In one embodiment, the content (in terms of solid content) of the (b2) component is 0 to 29% by mass relative to the total 100% by mass (in terms of solid content) of the (meth)acrylate constituting the (B) component. If the content (in terms of solid content) of the (b2) component exceeds 29% by mass, the adhesive surface tends to peel off when repeatedly folded, which is not preferable. The higher the content (in terms of solid content) of the (b2) component, the better the adhesive strength.

[0061] Examples of upper limits of the content ratio of the (A) component to the (B) component (mass ratio, solid content equivalent, [(A) component / (B) component]) are 70 / 30, 65 / 35, 60 / 40, 55 / 45, 50 / 50, 45 / 55, 40 / 60, 35 / 65, 30 / 70, 25 / 75, 20 / 80, and 15 / 85, while examples of lower limits include 65 / 35, 60 / 40, 55 / 45, 50 / 50, 45 / 55, 40 / 60, 35 / 65, 30 / 70, 25 / 75, 20 / 80, 15 / 85, and 10 / 90. In one embodiment, the content ratio of the (A) component to the (B) component (mass ratio, calculated as solid content, [(A) component / (B) component]) is preferably 40 / 60 to 65 / 35, more preferably 40 / 60 to 55 / 45, and even more preferably 40 / 60 to 50 / 50, from the viewpoints of haze value, storage modulus, and strain.

[0062] Examples of upper limits of the content of the (B) component (converted to solid content) relative to 100% by mass (converted to solid content) of the total amount of the (A) component, the (B) component, and the (C) components are 55, 54, 53, 52, 51, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, 35, 34, 33, 32, and 31% by mass, and examples of lower limits of the content of the (B) component (converted to solid content) relative to 100% by mass (converted to solid content) include 54, 53, 52, 51, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, and 30% by mass. In one embodiment, the content of the (B) component (solid content equivalent) in the total amount of the (A), (B) and (C) components (100 mass % solid content equivalent) is about 30 to 55 mass %. If the content of the (B) component is less than 30 mass %, bending property is deteriorated, which is not preferable. If the content of the (B) component is more than 55 mass %, curing failure occurs and processability is deteriorated, which is not preferable.

[0063] <(C) component> The (C) component is a primary hydroxyl group-containing mono(meth)acrylate. By using the (C) component, the adhesive composition has excellent curability, and the cured product has excellent durability after a moist heat resistance test. When a mono(meth)acrylate without a hydroxyl group is used as a substitute for the (C) component, the durability after the moist heat resistance test and the haze value after the moist heat resistance test are inferior. In addition, when a secondary hydroxyl group-containing mono(meth)acrylate is used as a substitute for the (C) component, the haze value after the moist heat resistance test is inferior. In this disclosure, the "haze value after moist heat resistance test" has the same meaning as that described in JP 2020-037689 A.

[0064] Examples of the component (C) include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and cyclohexanedimethanol mono(meth)acrylate.

[0065] The component (C) is preferably 2-hydroxyethyl (meth)acrylate and / or 4-hydroxybutyl (meth)acrylate, since the pressure-sensitive adhesive composition has excellent curing properties and the cured product has excellent durability after a moist heat resistance test.

[0066] Examples of the upper limit of the content ratio of the (A) component to the (C) component (mass ratio, solid content equivalent, [(A) component / (C) component]) are 90 / 10, 85 / 15, 80 / 20, 75 / 25, 70 / 30, 65 / 35, 60 / 40, 55 / 45, 50 / 50, 45 / 55, etc., and examples of the lower limit are 85 / 15, 80 / 20, 75 / 25, 70 / 30, 65 / 35, 60 / 40, 55 / 45, 50 / 50, 45 / 55, 40 / 60, etc. In one embodiment, the content ratio of the (A) component to the (C) component (mass ratio, solid content equivalent, [(A) component / (C) component]) is preferably about 40 / 60 to 80 / 20.

[0067] Examples of the upper limit of the content ratio of the (B) component to the (C) component (mass ratio, solid content equivalent, [(B) component / (C) component]) are 95 / 5, 90 / 10, 85 / 15, 80 / 20, 75 / 25, 70 / 30, 65 / 35, 60 / 40, 55 / 45, etc., and examples of the lower limit are 90 / 10, 85 / 15, 80 / 20, 75 / 25, 70 / 30, 65 / 35, 60 / 40, 55 / 45, 50 / 50, etc. In one embodiment, the content ratio of the (B) component to the (C) component (mass ratio, solid content equivalent, [(B) component / (C) component]) is preferably about 50 / 50 to 95 / 5.

[0068] The upper limit of the content (solid content) of the (C) component in 100% by mass (solid content) of the total of the (A) component, the (B) component, and the (C) component is 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, and 10% by mass, and the lower limit is 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, and 9% by mass. In one embodiment, the content (solid content) of the (C) component in 100% by mass (solid content) of the total of the (A) component, the (B) component, and the (C) component is preferably about 9% by mass or more and less than 20% by mass. If the content of the (C) component is less than 9% by mass, the adhesive strength decreases, which is not preferable. If the content of the (C) component is 20% by mass or more, the compatibility with other components decreases, and the b* value of the cured product increases, which is not preferable.

[0069] <(D) component> The pressure-sensitive adhesive composition of the present disclosure preferably contains a radical photopolymerization initiator (hereinafter also referred to as "component (D)") because the cured product has excellent curing properties.

[0070] Examples of the component (D) include alkylphenone type photopolymerization initiators, acylphosphine oxide type photopolymerization initiators, hydrogen abstraction type photopolymerization initiators, and oxime ester type photopolymerization initiators.

[0071] Examples of alkylphenone type photopolymerization initiators include benzyl dimethyl ketal (e.g., 2,2-dimethoxy-1,2-diphenylethan-1-one, etc.), α-hydroxyalkylphenone (e.g., 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, etc.), α-aminoalkylphenone (e.g., 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, etc.), and the like.

[0072] Examples of the acylphosphine oxide type photopolymerization initiator include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like.

[0073] An example of the hydrogen abstraction type photopolymerization initiator is phenylglyoxylic acid methyl ester.

[0074] Examples of oxime ester type photopolymerization initiators include 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime), and the like.

[0075] The component (D) is preferably an α-hydroxyalkylphenone type photopolymerization initiator and / or an acylphosphine oxide type photopolymerization initiator, since the pressure-sensitive adhesive composition has excellent curing properties.

[0076] Examples of the upper limit of the content (solid content) of the (D) component relative to 100% by mass (solid content) of the total amount of the (A), (B), and (C) components are 10, 9, 8, 7, 6, 5, 4, 3, 2, 1.5, 1, 0.5, and 0.2% by mass, and examples of the lower limit are 9, 8, 7, 6, 5, 4, 3, 2, 1.5, 1, 0.5, 0.2, and 0.1% by mass. In one embodiment, the content (solid content) of the (D) component relative to 100% by mass (solid content) of the total amount of the (A), (B), and (C) components is preferably 0.1% by mass or more and 3% by mass or less, more preferably 0.1% by mass or more and 2% by mass or less, and even more preferably 0.1% by mass or more and 1.5% by mass or less.

[0077] <Other additives that can be added> The pressure-sensitive adhesive composition of the present disclosure may contain various additives as necessary, such as a surface conditioner, a surfactant, an ultraviolet absorber, an antioxidant, a light stabilizer, an inorganic filler, a silane coupling agent, colloidal silica, an antifoaming agent, a wetting agent, an anti-rust agent, a plasticizer, a chain transfer agent, and a photosensitizer.

[0078] The adhesive composition of the present disclosure may contain a resin having a softening point of 90° C. or more as component (E). When the adhesive composition of the present disclosure contains component (E), the adhesive strength of the cured product is good, but if the content is too high, it adversely affects the bending resistance of the cured product. Therefore, the content (mass %) of component (E) calculated as solid content is preferably less than 10 mass %, more preferably less than 1 mass %, and even more preferably 0 mass %, when the total of components (A), (B), and (C) is taken as 100 mass %. Examples of component (E) include hydroxyl group-containing petroleum resin, disproportionated rosin resin, and hydrogenated rosin resin. In the present disclosure, the softening point is measured by the ring and ball method based on JIS K-2351. The upper limit of the softening point (°C) of the component (E) is exemplified as 150, 140, 130, 120, 110, 100, etc., and the lower limit is exemplified as 140, 130, 120, 110, 100, 90, etc.

[0079] The pressure-sensitive adhesive composition of the present disclosure may contain a coupling agent as component (F). By including component (F) in the pressure-sensitive adhesive composition of the present disclosure, adhesion to the substrate is improved. In particular, when the substrate is glass, a coupling agent having a reactive group that chemically bonds with an inorganic material and a reactive group that chemically bonds with an organic material is preferred as component (F) since adhesion is improved. Examples of such coupling agents include silane coupling agents. When the total of components (A), (B), and (C) is taken as 100% by mass, the upper limit of the content (mass%) of component (F) calculated as solid content is 10, 9, 8, 7, 6, 5, 4, 3, 2, and 1% by mass, and the lower limit is 9, 8, 7, 6, 5, 4, 3, 2, and 1% by mass. In one embodiment, the content (mass %) of the (F) component in terms of solid content, when the total of the (A), (B), and (C) components is taken as 100 mass %, is preferably 0 to 10 mass %.

[0080] The pressure-sensitive adhesive composition of the present disclosure may contain a solvent. Examples of the solvent include ketone solvents, aromatic solvents, alcohol solvents, glycol solvents, glycol ether solvents, ester solvents, petroleum-based solvents, haloalkane solvents, and amide solvents.

[0081] Examples of the ketone solvent include methyl ethyl ketone, acetylacetone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone.

[0082] Examples of aromatic solvents include toluene and xylene.

[0083] Examples of the alcohol solvent include methanol, ethanol, n-propanol, isopropanol, butanol, and the like.

[0084] Examples of glycol solvents include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, polyethylene glycol, and polypropylene glycol.

[0085] Examples of glycol ether solvents include ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol mono-n-butyl ether, ethylene glycol monoisobutyl ether, and ethylene glycol mono-t-butyl ether.

[0086] Examples of the ester solvent include ethyl acetate, butyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, and propylene glycol monomethyl ether acetate.

[0087] Examples of petroleum-based solvents include T-SOL 100 (manufactured by ENEOS Corporation) and T-SOL 150 (manufactured by ENEOS Corporation).

[0088] An example of the haloalkane solvent is chloroform.

[0089] An example of the amide solvent is dimethylformamide.

[0090] The pressure-sensitive adhesive composition of the present disclosure can be used without containing a solvent. Therefore, from the viewpoint of reducing costs and reducing the impact on the environment, the pressure-sensitive adhesive composition of the present disclosure preferably does not contain a solvent.

[0091] Examples of the upper limit of the viscosity (mPa·s / 25°C) of the pressure-sensitive adhesive composition of the present disclosure include 10,000, 9,000, 8,000, 7,000, 6,000, 5,000, 4,000, 3,000, 2,000, 1,000, 500, and 300, and examples of the lower limit include 9,000, 8,000, 7,000, 6,000, 5,000, 4,000, 3,000, 2,000, 1,000, 500, 300, and 100. The viscosity (mPa·s / 25°C) of the pressure-sensitive adhesive composition of the present disclosure is preferably 100 or more and 10,000 or less, more preferably 300 or more and 8,000 or less, and even more preferably 500 or more and 7,000 or less, since the pressure-sensitive adhesive composition has excellent handleability. In this disclosure, the viscosity is a value (5 minutes) measured using an E-type viscometer (product name "TVE-10", manufactured by Toki Sangyo Co., Ltd.).

[0092] The pressure-sensitive adhesive composition of the present disclosure can be obtained by mixing the components (A), (B), and (C), and optionally the components (D), (E), and (F), and other additives that can be added. The order of mixing is not particularly limited, and the components may be mixed sequentially or all at once.

[0093] <Cured product> The present disclosure also includes a product cured by irradiating the pressure-sensitive adhesive composition with active energy rays such as ultraviolet rays. When the pressure-sensitive adhesive composition contains a solvent, it is considered to perform a drying treatment before irradiating with ultraviolet rays. The pressure-sensitive adhesive composition may be applied to various substrates to form a layer of the pressure-sensitive adhesive composition, and then the layer may be irradiated with ultraviolet rays to obtain a cured product.

[0094] Examples of ultraviolet light sources include ultraviolet irradiation devices having a xenon lamp, a high-pressure mercury lamp, and a metal halide lamp. In the device, the conditions of the ultraviolet irradiation intensity, the integrated light amount, and the transport speed are usually as follows: irradiation intensity is 80 mW / cm 2 More than 160mW / cm 2 The conveying speed is 3 m / min to 50 m / min, and the cumulative light intensity is 100 mJ / cm 2 More than 3,000mJ / cm 2 The following is the result.

[0095] Examples of methods for applying the pressure-sensitive adhesive composition include bar coater coating, Mayer bar coating, air knife coating, gravure coating, reverse gravure coating, offset printing, flexographic printing, and screen printing.

[0096] The coating amount is usually 1g / m2 after drying. 2 More than 1,000g / m 2 Less than 3 g / m 2 More than 500g / m 2 The range is as follows.

[0097] The thickness of the cured product of the present disclosure is not particularly limited, but since the cured product exhibits favorable conformability to unevenness and is less likely to produce bubbles, the thickness of the coating film after drying is preferably from 10 μm to 1,000 μm, and more preferably from 25 μm to 500 μm.

[0098] The upper limit of the storage modulus of the cured product of the present disclosure at 23° C. and 1 Hz is exemplified as 150, 140, 130, 120, 110, 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 40, 30, 20 kPa, etc., and the lower limit is exemplified as 140, 130, 120, 110, 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 40, 30, 20, 10 kPa, etc. In one embodiment, the storage modulus of the cured product of the present disclosure at 23° C. and 1 Hz is preferably less than 150 kPa, more preferably less than 80 kPa, since the lower the storage modulus, the better the durability (also referred to as "repeated bending resistance" in the present disclosure) when the cured product is repeatedly bent in a room temperature environment (23° C.). In addition, the upper limit of the storage modulus at -15 ° C. and 1 Hz of the cured product of the present disclosure is exemplified as 400, 350, 300, 250, 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, etc., and the lower limit is exemplified as 350, 300, 250, 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, 100, etc. In one embodiment, the lower the storage modulus at -15 ° C. and 1 Hz of the cured product of the present disclosure, the better the durability (also referred to as "repeated bending resistance" in the present disclosure) when the cured product is repeatedly bent in a low temperature environment (-15 ° C.), so that it is preferably less than 400 kPa, more preferably less than 250 kPa.

[0099] The upper limit of the strain test value of the cured product of the present disclosure at 23° C. is 1000, 900, 800, 700, 600, 500, 400, 300, 200, etc., and the lower limit is 900, 800, 700, 600, 500, 400, 300, 200, 100, etc. In one embodiment, the strain test value of the cured product of the present disclosure at 23° C. is preferably 100 or more and 1000 or less, more preferably 200 or more and 900 or less, and even more preferably 300 or more and 800 or less. The upper limit of the numerical value of the strain test of the cured product of the present disclosure at -15 ° C. is 1000, 900, 800, 700, 600, 500, 400, 300, 200, 100, etc., and the lower limit is 900, 800, 700, 600, 500, 400, 300, 200, 100, 50, etc. In one embodiment, the numerical value of the strain test of the cured product of the present disclosure at -15 ° C. is preferably 50 or more and 1000 or less, more preferably 100 or more and 700 or less, and even more preferably 100 or more and 500 or less. By having a numerical value equal to or more than the lower limit, the cured product can withstand the strain generated when repeatedly bending the cured product, and by having a numerical value equal to or less than the upper limit, the adhesion of the cured product to the blade when cutting the cured product can be reduced, and the processability is also good.

[0100] <Molded object> An example of the application of the pressure-sensitive adhesive composition is its application between substrates of various known articles.

[0101] Examples of such articles include the main body of a home appliance such as a television and its remote control, and the housing and display of an information terminal such as a mobile phone, a smartphone, a tablet, or a personal computer.

[0102] The active energy ray curable pressure-sensitive adhesive composition of the present disclosure is suitable for optical applications, and is preferably used as an optically transparent adhesive (OCA). For example, it can be applied to a multi-layered display panel in a digital display device. In addition, the cured product of the present disclosure has excellent bending resistance, and therefore can be used particularly for foldable devices.

[0103] <Applicable substrates> Examples of substrates to which the pressure-sensitive adhesive composition of the present disclosure is applied include glass substrates, plastic substrates, paper substrates, cloth substrates, rubber sheet substrates, foam sheet substrates, metal substrates, etc. Examples of plastic substrates include thermoplastic plastic substrates and thermosetting plastic substrates, etc. Examples of thermoplastic plastic substrates include general-purpose plastic substrates and engineering plastic substrates, etc. Examples of general-purpose plastic substrates include olefin-based, polyester-based, acrylic-based, vinyl-based, polystyrene-based, etc. Examples of olefin-based substrates include polyethylene, polypropylene, norbornene, etc. Examples of polyester-based substrates include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polylactic acid (PLA), polyhydroxyalkanoic acid (PHA), polycaprolactone (PCL), etc. Examples of acrylic-based substrates include polymethyl methacrylate (PMMA), etc. Examples of vinyl-based materials include polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, etc. Examples of polystyrene-based materials include polystyrene (PS) resin, styrene-acrylonitrile (AS) resin, styrene-butadiene-acrylonitrile (ABS) resin, etc. Examples of engineering plastic substrates include general-purpose engineering plastics and super engineering plastics. Examples of general-purpose engineering plastics include polycarbonate and polyamide (nylon). Examples of super engineering plastics include polyether ether ketone (PEEK). Examples of thermosetting plastic substrates include polyimide, epoxy resin, melamine resin, etc. Examples of other plastic substrates include triacetyl cellulose resin, etc. Examples of paper substrates include Japanese paper, craft paper, glassine paper, fine paper, synthetic paper, topcoat paper, etc. Examples of cloth substrates include woven fabrics and nonwoven fabrics made by spinning various fibrous materials alone or in a mixture. Examples of rubber sheet substrates include natural rubber, butyl rubber, etc. Examples of the foam sheet substrate include foamed polyurethane, foamed polychloroprene rubber, etc. Examples of the metal substrate include aluminum foil, copper foil, etc.The substrate may be one that has been subjected to a surface treatment (corona discharge, etc.). In addition, other layers (e.g., an easy-adhesion layer, an anchor layer, etc.) may be provided between the layer of the pressure-sensitive adhesive composition of the present disclosure and one or both sides of the substrate. The substrate is preferably a substrate used for optical purposes. Examples of optical substrates include polyester films such as polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate (PEN), polyethylene films, polypropylene films, cellophane, diacetyl cellulose films, triacetyl cellulose films, acetyl cellulose butyrate films, polyvinyl chloride films, polyvinylidene chloride films, polyvinyl alcohol films, ethylene-vinyl acetate copolymer films, polystyrene films, polycarbonate films, polymethylpentene films, polysulfone films, polyether ether ketone films, polyether sulfone films, polyether imide films, polyimide films, fluororesin films, polyamide films, acrylic resin films, norbornene-based resin films, and plastic films such as cycloolefin resin films, glass, tin-doped indium oxide films, ITO films, and transparent conductive films. The thickness of the substrate is not particularly limited, and is usually about 30 to 300 μm.

[0104] Specifically, the combination of the cured product of the present disclosure and the substrate for optics is as follows: (1) Substrate, cured product of the present disclosure, transparent conductive film (also referred to as "ITO" in the present disclosure) (2) Substrate, cured product of the present disclosure, and liquid crystal display etc. are examples. EXAMPLES

[0105] The present disclosure will be described in more detail below with reference to Production Examples, Comparative Production Examples, Examples, Comparative Examples, Evaluation Examples, and Comparative Evaluation Examples, but the present disclosure is not limited to these Examples. In the following description, parts and % are based on mass.

[0106] In the present examples, the weight average molecular weight (Mw) was measured by gel permeation chromatography (GPC) under the following conditions. (GPC measurement conditions) Model: Product name "HLC-8220GPC" (manufactured by Tosoh Corporation) Column: Product name "TSKgel G1000H" "TSKgel G2000H" (manufactured by Tosoh Corporation) Developing solvent: Tetrahydrofuran Flow rate: 0.6mL / min Measurement temperature: 40℃ Detector: Refractive Index Detector (RI) Standard: Monodisperse polystyrene Sample: A tetrahydrofuran solution of 0.2% solid content was prepared from the resin, and 20 μL of the solution was obtained by filtering the solution through a microfilter.

[0107] In each production example, the NCO value of the urethane prepolymer was measured by the following method. Measuring device: Automatic potentiometric titrator (product name "AT-400", manufactured by Kyoto Electronics Manufacturing Co., Ltd.) Measurement steps: 1: Weigh out approximately 0.500g to 1.000g of sample into a weighing bottle. 2: Inject 10 mL of 0.15 mol / L dibutylamine solution in toluene. 3: Place the weighing bottle containing the sample in an ultrasonic cleaner to completely dissolve the sample. 4: Make sure the sample is completely dissolved and leave it for 15 minutes (away from direct sunlight and heat). 5: After 15 minutes, add 100 mL of isopropyl alcohol to the weighing bottle. Place the stirrer piece in the weighing bottle. 6: Titrate using 0.1 mol / L hydrochloric acid solution (f=1.00) to determine the NCO value. Input the amount of sample to be measured into the automatic titrator and then measure. If the measurement difference is within 0.30, it is acceptable. If it is 0.30 or more, measure one sample again to confirm that it is within 0.30.

[0108] <Production Example 1: Preparation of component (A-1)> A reaction apparatus equipped with a cooling tube, a stirrer, and a nitrogen inlet tube was charged with 884 parts of polypropylene glycol having a number average molecular weight of 2000 (product name "ADEKA Polyether P-2000" (in this disclosure, also referred to as "PPG2000"), manufactured by ADEKA Corporation), 106 parts of isophorone diisocyanate (in this disclosure, also referred to as "IPDI"), 333 parts of 2-ethylhexyl acrylate (in this disclosure, also referred to as "2EHA"), and 0.4 parts of stannous octoate, and the mixture was heated to 80°C and maintained at that temperature for 3 hours, yielding a 2EHA solution of an isocyanate group-terminated urethane prepolymer intermediate. Next, 10 parts of 4-hydroxybutyl acrylate (also referred to as "4HBA" in this disclosure) was added, and the mixture was kept at 80°C for 2 hours. Completion of the reaction was confirmed by NCO measurement, thereby obtaining a 2EHA solution of polyurethane acrylate (A-1) (also referred to as "component (A-1)" in this disclosure) having a weight average molecular weight of 55,000, an average number of acryloyl groups of 2, and an acrylic equivalent of 27,500.

[0109] <Example 1: Preparation of adhesive composition (1)> A pressure-sensitive adhesive composition (1) was obtained by mixing 37 parts of the (A-1) component, 53 parts of 2-EHA as the (B) component, 10 parts of 4HBA as the (C) component, and 1 part of 1-hydroxycyclohexyl-phenyl ketone (product name "Omnirad 184" (also referred to as "Omni 184" in this disclosure), manufactured by IGM Resins) as the (D) component.

[0110] <Examples 2 to 6 and Comparative Examples 1 to 6: Pressure-sensitive adhesive compositions (2) to (6) and pressure-sensitive adhesive compositions (C1) to (C6)> The same procedure as in Example 1 was repeated except that the components were changed as shown in Table 1.

[0111] <Performance evaluation (1): Adhesive strength> Each of the pressure-sensitive adhesive compositions (1) to (6) and (C1) to (C6) was applied onto a 75 μm thick polyester film treated with a heavy release agent (product name "SP-PET-03-75BU", manufactured by PANAC Corporation) so that the thickness of the adhesive layer after curing would be 50 μm. The release-treated surface of a 38 μm thick polyester film treated with a light release agent (product name "SP-PET-01-38BU", manufactured by PANAC Corporation) was then bonded to the pressure-sensitive adhesive composition coating layer. The resulting coated film was then exposed to a high-pressure mercury lamp (100 mW / cm) in the atmosphere. 2 , 2,000mJ / cm 2 ), a laminated film including an adhesive layer (light release treated polyester film / adhesive layer / heavy release treated polyester film) was produced. Next, the light release treated polyester film was peeled off, and instead, a 50 μm thick polyester film (product name "Cosmoshine A-4300", manufactured by Toyobo Co., Ltd.) was attached with a 2 kg roller and left to stand for 2 hours. Next, a test piece of 2.5 cm × 10 cm was cut from this, and the heavy release treated polyester film was peeled off to produce a single-sided adhesive sheet (Cosmoshine A-4300 / adhesive layer). A single-sided adhesive sheet (adhesive layer / Cosmoshine A-4300) (2.5 cm×10 cm×150 μm) was placed on a glass plate (2.5 cm×12 cm×2 mm) and pressed against it with a 2 kg roller to produce a laminate (Cosmoshine A-4300 (50 μm thick) / adhesive layer (50 μm thick) / glass plate (2 mm thick)) (laminates (1) to (6) and (C1) to (C6)). The laminates (1) to (6) and (C1) to (C6) were left to stand for 24 hours under conditions of 25° C. and 50% humidity. The single-sided adhesive sheet (adhesive layer / Cosmoshine A-4300) was peeled off from the glass plate in a 180° direction at a speed of 300 mm / min to measure the adhesive strength (N / 25 mm) and evaluate according to the following criteria. For the measurements, a commercially available machine (product name "Tensilon Universal Material Testing Machine", manufactured by AND Co., Ltd.) was used. 〇: More than 5N ×: 5N or less

[0112] <Performance evaluation (2): Total light transmittance> The total light transmittance (%) of the laminates (1) to (6) and (C1) to (C6) was measured using a commercially available measuring device (product name "Haze Transmittance Meter HM-150", manufactured by Murakami Color Research Laboratory Co., Ltd.) in accordance with the single beam method described in JIS K 7361-1:1997, and evaluated according to the following criteria. 〇: Over 90% ×: Less than 90%

[0113] <Performance evaluation (3): Haze value> The haze values ​​of the laminates (1) to (6) and (C1) to (C6) were measured in accordance with JIS K 7136:2000 using a commercially available measuring device (product name "Haze / Transmittance Meter HM-150", manufactured by Murakami Color Research Laboratory Co., Ltd.), and evaluated according to the following criteria. ○: Less than 0.15% △: 0.15% or more and less than 0.3% ×: 0.3% or more

[0114] <Performance evaluation (4): Chromaticity b* value> For the laminates (1) to (6) and (C1) to (C6), b* in the CIE1976L*a*b* color system was measured in accordance with JIS Z8781-4:2013, and evaluated according to the following criteria. ○: Less than 0.4% ×: 0.4% or more

[0115] <Performance evaluation (5): Glass transition temperature> The pressure-sensitive adhesive compositions (1) to (6) and (C1) to (C6) were measured using a measuring device (product name "MCR302", manufactured by Anton Paar). The loss modulus (G'') / storage modulus (G') was expressed as loss tangent, and the temperature at the peak top of the loss tangent was taken as the glass transition temperature. The glass transition temperature was evaluated according to the following criteria. ○: Less than -40℃ △: -40℃ or higher, less than -30℃ ×: -30℃ or higher

[0116] <Performance Evaluation (6): Storage Modulus> Each of the pressure-sensitive adhesive compositions (1) to (6) and (C1) to (C6) was applied onto a 75 μm thick heavy release treated polyester film (product name "SP-PET-03-75BU", manufactured by Mitsui Chemicals Tohcello Co., Ltd.) so that the film thickness of the cured product after curing was 50 μm, and the release treated surface of a 38 μm thick light release treated polyester film (product name "SP-PET-01-38BU", manufactured by Mitsui Chemicals Tohcello Co., Ltd.) was laminated to the pressure-sensitive adhesive composition coating layer. Next, the obtained coated film was exposed to a high pressure mercury lamp (100 mW / cm) in the atmosphere. 2 , 2,000mJ / cm 2 ), a laminate (light release treated polyester film / cured product / heavy release treated polyester film) containing a cured product was produced. Next, a 1 cm x 1 cm test piece was cut out from the laminate. Next, the light release treated polyester film and the heavy release treated polyester film were peeled off from the test piece to obtain cured products (1) to (6) and (C1) to (C6). 20 layers of 50 μm cured product were laminated to obtain a sample with a thickness of 1 mm. The sample was punched out to a diameter of 8 mm, and measurement samples (1) to (6) and (C1) to (C6) were obtained. The measurement samples (1) to (6) and (C1) to (C6) were subjected to a commercially available measuring device (product name "MCR302", manufactured by Anton Paar) to measure their dynamic viscoelasticity under the following conditions. From the measurement results, the storage modulus at -15°C and 1 Hz and the storage modulus at 23°C and 1 Hz were measured and evaluated according to the following criteria. (Measurement conditions) Deformation mode: Torsion Measurement frequency: 1Hz Distortion: 0.01~1% AUTO setting Heating rate: 3℃ / min Measurement temperature: -80~100℃ Shape: Parallel plate 8.0mmφ (Storage modulus at -15℃ and 1Hz) ○: Less than 250kPa △: 250kPa or more and less than 400kPa ×: 400kPa or more (Storage modulus at 23℃ and 1Hz) ○: Less than 80kPa △: 80kPa or more and less than 150kPa ×: 150kPa or more

[0117] <Performance evaluation (7): Strain test> The cured products (1) to (6) and (C1) to (C6) were measured using a measuring device (product name "MCR302", manufactured by Anton Paar). <Creep test> A shear stress of 40 kPa was applied to the cured product for 10 minutes at -15° C. or 23° C. The amount of distortion of the cured product after 10 minutes was evaluated according to the following criteria. (-15℃ strain) 〇: 100 or more and 500 or less △: 50 or more but less than 100, or more than 500 but less than 1000 ×: Less than 50 or more than 1000 (23°C strain) 〇: 300 or more and 800 or less △: 100 or more but less than 300, or 800 or more but less than 1000 ×: Less than 100 or more than 1000

[0118] [Table 1]

[0119] The terms in Table 1 have the following meanings: The values ​​for the content of each component in the table are calculated as solid content. UA: Polyurethane acrylate obtained in Production Example 1 2EHA: 2-Ethylhexyl acrylate (product name: 2-Ethylhexyl acrylate, manufactured by Mitsubishi Chemical Corporation) NOAA: normal octyl acrylate (product name: "NOAA", manufactured by Osaka Organic Chemical Industry Co., Ltd.) FA-513AS: Dicyclopentanyl acrylate (product name "FA-513AS", manufactured by Showa Denko Materials Co., Ltd.) 4HBA: 4-hydroxybutyl acrylate (product name "4-HBA", manufactured by Osaka Organic Chemical Industry Co., Ltd.) Omni 184: 1-Hydroxycyclohexyl-phenyl ketone (product name "Omnirad 184", manufactured by IGM Resins) KE-100: Ultra-light-colored rosin ester (product name: Pine Crystal KE-100, manufactured by Arakawa Chemical Industries, Ltd.) Coupling agent: 3-methacryloxypropylmethyldimethoxysilane (product name "KBM-502", Shin-Etsu Chemical Co., Ltd.)

Claims

1. (A) a urethane (meth)acrylate (A) which is a reaction product of (a1) a polyether polyol, (a2) a linear aliphatic diisocyanate and / or an alicyclic aliphatic diisocyanate, and (a3-1) a hydroxyl group-containing mono(meth)acrylate or (a3-2) an isocyanate group-containing mono(meth)acrylate and has a weight average molecular weight of 50,000 or more and 110,000 or less; (B) a (meth)acrylate having one ethylenically unsaturated double bond and no hydroxy group in the molecule; (C) a primary hydroxyl group-containing mono(meth)acrylate, the component (B) contains a (meth)acrylate (b1) having a glass transition temperature of less than −5° C. when made into a homopolymer and / or a (meth)acrylate (b2) having a glass transition temperature of −5° C. or higher when made into a homopolymer, The component (b1) is at least one selected from the group consisting of tetradecyl methacrylate, 2-ethylhexyl acrylate, ethoxydiethylene glycol acrylate, isooctyl acrylate, ethyl carbitol acrylate, n-octyl acrylate, lauryl methacrylate, isononyl acrylate, n-butyl acrylate, 2-methoxyethyl acrylate, isodecyl methacrylate, nonyl acrylate, 2-ethoxyethyl methacrylate, isobutyl acrylate, n-lauryl acrylate, phenoxyethyl acrylate, isostearyl acrylate, 2-ethylhexyl methacrylate, and (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate; the component (b2) is at least one selected from the group consisting of 2-methoxyethyl methacrylate, (3-ethyloxetan-3-yl)methyl methacrylate, benzyl acrylate, methyl acrylate, cyclohexyl acrylate, diethylaminoethyl methacrylate, dimethylaminoethyl methacrylate, n-butyl methacrylate, cyclic trimethylolpropane formal acrylate, n-stearyl acrylate, n-stearyl methacrylate, t-butyl acrylate, glycidyl methacrylate, isobutyl methacrylate, 3,3,5-trimethylcyclohexyl acrylate, benzyl methacrylate, tetrahydrofurfuryl methacrylate, glycidyl acrylate, ethyl methacrylate, cyclohexyl methacrylate, isobornyl acrylate, methyl methacrylate, t-butyl methacrylate, dicyclopentanyl acrylate, 1-adamantyl acrylate, and 1-adamantyl methacrylate; The component (C) is at least one member selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and cyclohexanedimethanol mono(meth)acrylate, When the total amount of the components (A), (B), and (C) is 100 mass%, The content of the component (A) in terms of solid content is more than 35% by mass and not more than 55% by mass, The content of the component (B) in terms of solid content is 40% by mass or more and 55% by mass or less, The content of the component (C) in terms of solid content is 9% by mass or more and 15% by mass or less, When the total amount of the (meth)acrylate constituting the component (B) is 100 mass%, The content of the component (b1) in terms of solid content is 71% by mass or more and 100% by mass or less, The content of the component (b2) in terms of solid content is 0% by mass or more and 29% by mass or less; An active energy ray-curable pressure-sensitive adhesive composition.

2. 2. The active energy ray-curable pressure-sensitive adhesive composition according to claim 1, which does not contain 1 mass% or more of a resin having a softening point of 90° C. or higher, relative to 100 mass% of the total of the components (A), (B), and (C).

3. A cured product of the active energy ray-curable pressure-sensitive adhesive composition according to claim 1 or 2.

4. A pressure-sensitive adhesive sheet having the cured product according to claim 3 on at least one surface of a substrate.

Citation Information

Patent Citations

  • Ultraviolet-curable adhesive, cured material, and adhesive sheet

    JP2018039999A

  • Ultraviolet-curable adhesive composition for protective film, adhesive layer, and protective sheet

    JP2019044183A

  • Active energy ray-curable adhesive composition, cured product and adhesive sheet

    JP2020037689A